Microbial Analysis of Chicken “Urutan” Traditional Food with Different Smoke Processes - A.A. Made Semariyani; I Wayan Sudiarta; Ni Made Ayu Suardani Singapurwa; Luh Suariani; Agata Viani; Sang Ayu Made Agung Prasetiawati Djelantik (International Journal of Scientific Multidisciplinary Research, 2023)
The chicken sequence is a processed meat product that is processed by making a complete Balinese meat, fat, and seasoning mixture and then put into a sleeve. This study aimed to investigate the impact of varying concentrations of coconut shell liquid smoke on the sequence features of chickens. The method used in this study is the descriptive analysis of microbial growth observations. The results showed that the use of coconut shell liquid smoke with a concentration of 4% could maintain chicken “urutan” for up to 20 days of storage at low temperatures (5+1 oC) with total microbial characteristics of 2.08 x 107 CFU/g, Escherichia coli < 103 CFU/g and Yeast mold 0 CFU/g (meet the requirements SNI 01-3820-2015)